Rancang Bangun Pengukur Jumlah Denyut Jantung, Kadar Oksigen Dalam Darah Dan Suhu Tubuh Berbasis Internet Of Things (Iot) - Dwipayana, I Made Agus Adi; Pramaita, I Nyoman; Setiawan, Widyadi (Teknik Desain Mekanika, 2022)
Abstract COVID-19 has a unique symptom called happy hypoxia syndrome which is found in some patients, in this condition the patient looks normal, does not have a cough or fever, but his oxygen saturation continues to drop if not treated immediately, the patient can die. Doctors recommend that home-treated COVID-19 patients have a heart rate meter or remote oxygen saturation meter. Therefore, remote monitoring is necessary to determine the patient's condition. To overcome this problem, the author wants to develop a thesis with the title "Design of measuring the amount of heart rate, blood oxygen levels and body temperature based on the Internet of Things (IoT)". This system works by detecting the patient's fingers which are then read by the body temperature and heart rate sensors then the detection results will be sent to the ThingSpeak cloud and will be displayed on the Smartphone screen. The prototype design for measuring the number of heart rates, blood oxygen levels and body temperature based on IoT is able to run according to the design. Key Words : Body Temperature, Heart Rate, Blood Oxygen Levels, Internet Of Things, MLX90614, MAX30100, ESP32